Grammatical Complexity and Gesture Production of Younger and Older Adults - Burcu ARSLAN; Demet ÖZER; Tilbe GÖKSUN (Dilbilim Araştırmaları Dergisi)
Age-related effects are observed in both speech and gesture production. Older adults produce grammatically fewer complex sentences and use fewer iconic gestures than younger adults. This study investigated whether gesture use, especially iconic gesture production, was associated with the syntactic complexity within and across younger and older age groups. We elicited language samples from these groups, using a picture description task (N=60). Results suggested shorter and less complex speech for older than younger adults. Although the two age groups were similar in overall gesture frequency, older adults produced fewer iconic gestures. Overall gesture frequency, along with participants’ ages, negatively predicted grammatical complexity. However, iconic gesture frequency was not a significant predictor of complex syntax. We conclude that each gesture might carry a function in a coordinated multimodal system, which might, in turn, influence speech quality. Focusing on individual differences, rather than age groups, might unravel the nature of multimodal communication.